2021
DOI: 10.1039/d1ta05242j
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ligands on the synthesis and application of metal halide perovskite nanocrystals

Abstract: The surface ligation of metal halide perovskite nanocrystals (NC) influences the size/dimensionality, optoelectronic properties, chemical stability, and use of the NCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 215 publications
1
78
0
Order By: Relevance
“…[19] Whereas the majority of BBA À are preferentially maintained on the surface of CPB QDs due to its relatively short chain structure, thus, resulting in the formation of a protective shell. [23][24][25][26] Those samples free of BBA or with only BBA quench completely as depicted in Figure 1a. Thereby, both BBA and OLA are jointly essential for the bright green luminescence of CPB QDs.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…[19] Whereas the majority of BBA À are preferentially maintained on the surface of CPB QDs due to its relatively short chain structure, thus, resulting in the formation of a protective shell. [23][24][25][26] Those samples free of BBA or with only BBA quench completely as depicted in Figure 1a. Thereby, both BBA and OLA are jointly essential for the bright green luminescence of CPB QDs.…”
Section: Resultsmentioning
confidence: 89%
“…It is believed that significant bonding interactions exist between the edge ions on the crystal structures of CPB QDs and the functional groups in organic ligands. [25,26] The obtained CPB QDs have been investigated by TEM as depicted in Figure 2a. It is observed that the pure CPB QDs of � 10 nm with a square-shape are well crystallized and monodispersed due to the presence of H 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the ligand modification has been reported as an effective method to enhance the long‐term stability of CsPbBr 3 NCs. [ 34–38 ] Huang et al. reported that multiple ionic liquids enable to facilitate stable perovskites.…”
Section: Introductionmentioning
confidence: 99%